2020
DOI: 10.1038/s41587-019-0374-x
|View full text |Cite
|
Sign up to set email alerts
|

An integrated perfusion machine preserves injured human livers for 1 week

Abstract: tandard preservation of donor livers is performed by flushing the organ with a cold solution at the time of procurement, which is followed by static storage on ice. This approach reduces liver metabolic activity, allowing safe storage for up to 12-18 h (refs. 1,2). Recently, the combination of supercooling with subzero storage (−4 °C) and hypothermic, as well as subnormothermic, machine perfusion achieved an extension of the preservation time of human livers up to 27 h (ref. 2). By contrast, human livers can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
373
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(404 citation statements)
references
References 40 publications
6
373
0
2
Order By: Relevance
“…Notably, the cold storage control group achieved a 96% one-year survival rate [55,56]. A development in the NMP technique that allowed a 7-day preservation of human livers with sustained metabolic function and intact liver structure was recently reported by Eshmuminov et al [57]. Based on the sustained full hepatic metabolism during NMP, several groups are currently exploring the possibility of normothermic viability testing [58].…”
Section: History and Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the cold storage control group achieved a 96% one-year survival rate [55,56]. A development in the NMP technique that allowed a 7-day preservation of human livers with sustained metabolic function and intact liver structure was recently reported by Eshmuminov et al [57]. Based on the sustained full hepatic metabolism during NMP, several groups are currently exploring the possibility of normothermic viability testing [58].…”
Section: History and Clinical Applicationmentioning
confidence: 99%
“…Pushing the boundaries and exploring the potentials of MP technology-such as the seven-day perfusion of human livers with preserved function and intact liver structure [57]-raise the question of the limits of this technological development. The enthusiasm for MP has to be viewed in the context of the limitations of the current technologies, which need to be defined clearly and early enough through clinical and translational efforts.…”
Section: Future Outlook and Remaining Challengesmentioning
confidence: 99%
“…(49) The recently published study by Eshmuminov et al shows that the majority of livers can maintain bile production during 7-day NMP stimulated by ursodeoxycholic acid infusion. (50) Whether or not infusion of bile acids also attenuates ischemia/reperfusion injury is still under investigation. (51,52) In a porcine LT model, it was shown that a lower bile/perfusate glucose ratio (<0.6) and a higher bile/ perfusate sodium ratio (≥1.2) during NMP was observed in DBD donors or donors with short warm ischemia (up to 70 minutes) compared with donors with long warm ischemia (120 minutes).…”
Section: Bile Composition Of the Donor Graft: During Machine Perfusiomentioning
confidence: 99%
“…At the time of donor procurement ↑ PC Identify steatotic grafts (41) ↓ Choleretic activity Identify suboptimal grafts (10) ↓ CA/CDCA ratio Identify suboptimal grafts (34) During NMP HCO − 3 >18 mmol/L, pH >7.48, glucose <16 mmol/L, bile/perfusate glucose ratio <0.67, and LDH concentration <3689 U/L Predict low histological degree of bile duct injury (2) Bile production >10 mL and pH >7.45 Predict bile duct viability (14) pH <7.85 Predict NAS (16) pH <7.4 Predict NAS (53) After transplantation ↓ Na + and ↑ bile glucose-blood glucose Predict NAS (12) ↓↓↓ Lipids Identify PNF (24) ↑ CDmiR Predict ACR (26) ↑ miR-133a, miR-148a, and miR-194 Predict ACR (27,31,46,49,50) ↑ IL2, IL6, and IL8 Predict ACR (30)(31)(32) ↑ CXCL9/10 Predict ACR (27,33) ↓ Bile salt, phospholipids, and cholesterol during the first week after LT Predict NAS (35) ↑ Bile salt/phospholipid ratio during the first week after LT Predict histologically severe bile duct injury (37) ↑ miR-517a, miR-106a, and miR-892a…”
Section: Bile Composition Goalmentioning
confidence: 99%
“…As the inflammatory cascade takes changes over time and stretches from minutes to hours and day, prolonged perfusion could be valuable. In that light, it is worthwhile to mention that 24-hour perfusion of discarded kidneys has been described [55], and recently, discarded human livers have been sustained ex situ for one week on normothermic perfusion [139].…”
Section: The Immune Cell Compartmentmentioning
confidence: 99%